How to Design a Perfect City. - Cass, S.
This paper presents one of Paolo Soleri's latest concepts, the Lean Linear City. Designed for the burgeoning urban populations of China, it stretches for hundreds of kilometers along the spine of a high-speed rail corridor to form a continuous structure in which people live, work and play. Photovoltaic cells and windmills help power the city
Keywords: China; Lean Linear City; Arcologies; City-as-system approach; High-speed rail corridor; Photovoltaic cells; Windmills